KAJIAN PENYUSUNAN PETA RISIKO PENURUNAN TANAH DI KOTA BANDUNG - Sudarsono, Ramdan
Land subsidence is a phenomenon that often occurs in big cities in Indonesia. This can happen because of the high population density which indicates the amount of ground water use and the amount of land built in an area. There are also natural factors that cause land subsidence such as soil structure and tectonic activity. In the city of Bandung, land subsidence reaches 14 cm per year. If left unchecked, this phenomenon can become an obstacle in the development process. Therefore, it is necessary to have mitigation efforts to reduce the reduction of this land subsidence. This study aims to study land subsidence in the city of Bandung, as well as to create a risk map. The hazard of land subsidence is assessed by analyzing the value of land subsidence based on previous research data. The value of land subsidence is compared with the level of damage to buildings according to the taxonomy of buildings obtained through field activities. The comparison is analyzed to produce the fragility and vulnerability curves of the soil which are used to determine the settlement of certain types of buildings in soil intensity. The making of a hazard index is based on the value of soil subsidence in previous studies. The index will be made based on the constituent components, namely social, physical, and economic. The vulnerability value is used to obtain the number of exposed population, the vulnerability value is used to obtain the amount of physical loss, and the vulnerability of the economic value is used to obtain the amount of economic loss. Hazard index and vulnerability index will be used for risk index assessment. The study of making land subsidence risk maps in the city of Bandung produces several outputs, namely the fragility and vulnerability curves which can be a multiplier factor for physical losses. There were also losses due to land subsidence in Bandung of 309 billion Rupiah and economic loss of 1.55 billion Rupiah. Areas with high land subsidence risk include Babakan Ciparay, Bandung Kidul, Batununggal, Bojongloa Kidul, Buahbatu, Gedebage, Rancasari and Regol.